Detection of Highway Lane using Color Filtering and Line Determination - Iwan Muhammad Erwin; Dicky Rianto Prajitno; Esa Prakasa (Khazanah Informatika, 2022)
Traffic accidents are generally caused by human error as a driver. The main cause is that the vehicle shifts away from the driving lane without the driver realizing it. Usually, because the driver is sleepy or drunk. Therefore, it is necessary to have a system that functions to assist the driver's navigation to stay on the correct driving path, such as a driver assistance system (DAS). In this system, the driving lane detector is the main part. This system serves to assist the driver's navigation to stay on the correct driving path. Vehicles are installed with cameras to record video towards the road ahead. Computers are also installed for image processing, identifying left and right road lines, and forming ego-lane. This paper offers an image processing-based method for recognizing driving lanes and presenting visualizations in real-time. This method has been tested using a data set, that video driving on Indonesian highway on the Cipali and Palikanci sections using dashboard camera. The test results obtained an accuracy of 99.25%.